Identifikasi Interferensi Berbahasa dalam Implementasi Hasil Penelitian Bidang Biologi yang Dituangkan dalam Bentuk Laporan - Siahaan, Erince Yonanda; Siregar, Rizka Juliana; Oktavia, Putri; Saurina, Theresia; Sitanggang, Yesaya Hasudungan; Febrina, Ika (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research aims to identify and analyze the forms of language interference that occur in biology research reports. Language interference is the phenomenon of elements from another language entering the language being used, which can reduce the quality and clarity of information delivery. Using a qualitative approach and content analysis method, this research analyzes biology practicum reports written by students. The results show various forms of language interference, such as phonological, morphological, syntactic, and semantic interference. The contributing factors of interference are identified, including the influence of the mother tongue, inadequate language proficiency, as well as social and situational factors. The findings of this research provide insights for researchers and related institutions to improve the quality of research report writing in the field of biology.